Plio-Pleistocene reef diversity in the Sulu Sea Sabah: Implications for the development of the Indo-Pacific Centre of Diversity - Saw, J.; Hunter, Aaron; Johnson, K. (2012)
The Sulu Sea of north-east Borneo is part of the biodiversity hotspot in the Malay Archipelago of South East Asia, also known as the “Indo-Pacific Centre of Diversity” (IPCD). Despite its apparent significance, the origins and evolution of this area remain poorly documented (McMonagle et al., 2011). Extensive reconnaissance studies by the Geological Survey of British Territories in Borneo in the mid-20th century and more recently by John Noad (see Noad 2001) have revealed several well preserved, high diversity faunal localities across north-east Sarawak and central and eastern Sabah ranging from the Oligocene-Miocene to the Plio-Pleistocene. The Dent Peninsula of eastern Sabah preserves Plio-Pleistocene sedimentary sequences, seldom found in Borneo, that represent localised transgressive episodes. Early results have revealed both a rich coral fauna, and associated bivalves and echinoderms. The aim of this research is to systematically sample these Plio-Pleistocene assemblages from the Dent Peninsula, Sabah, including a detailed study of the sedimentary facies to determine the palaeobiodiversity and possible palaeoecological zonation of these assemblages including their fidelity. We also intend to compare these with adjacent Recent assemblages (such as Dent Heaven and Semporna, Sabah) to establish how much the assemblages are reflected in the Recent diversity. Finally we will track the development and evolution of reef habitats of the Dent Peninsula from the Plio-Pleistocene to Recent in order to determine the existence of Plio-Pleistocene extinction or recovery events in the IPCD. This research will provide a fundamental understanding of the coral reef diversity, growth and evolution of the Sulu Sea, Sabah, in the late Neogene and provide a framework for exploring the driving factors behind the IPCD hotspot of biodiversity.